The effect of LiCF3SO3 on the complexation with potato starch-chitosan blend polymer electrolytes - Amran, N.N.A.; Manan, N.S.A.; Kadir, M.F.Z. (Springer Verlag (Germany), 2016)
This work examines the effect of lithium trifluoromethanesulfonate (LiCF3SO3) and glycerol on the conductivity and dielectric properties of potato starch-chitosan blend-based electrolytes. The electrolytes are prepared via solution cast technique. From X-ray diffraction (XRD) analysis, the blend of 50Â wt.% starch and 50Â wt.% chitosan is found to be the most amorphous blend. Fourier transform infrared (FTIR) spectroscopy studies show the interaction between the electrolyte materials. The room temperature conductivity of pure starch-chitosan film is found to be (2.85Â Â±Â 1.31)Â Ã—Â 10−10Â SÂ cm−1. The incorporation of 45Â wt.% LiCF3SO3 increases the conductivity to (7.65Â Â±Â 2.27)Â Ã—Â 10−5Â SÂ cm−1. Further conductivity enhancement up to (1.32Â Â±Â 0.35)Â Ã—Â 10−3Â SÂ cm−1 has been observed on addition of 30Â wt.% glycerol. This trend in conductivity is verified by XRD and dielectric analysis. The temperature dependence of conductivity of all electrolytes are Arrhenian.